Tolerance to future elevated CO2 conditions in sablefish (Anoplopoma fimbria), a deep-water benthic dwelling fish species - Chase R. Williams; Evan P. Gallagher; Paul McElhany; D. Shallin Busch; Michael T. Maher; Andrew H. Dittman (Journal of Comparative Physiology A, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Interactive roles of temperature and food availability in predicting habitat suitability for marine invertebrates - Raymond Czaja; Brian Beal; Kyle Pepperman; Emmanuelle Pales Espinosa; Daphne Munroe; Robert Cerrato; Evan Busch; Bassem Allam (Estuarine, Coastal and Shelf Science, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Elevated CO 2 impairs olfactory‐mediated neural and behavioral responses and gene expression in ocean‐phase coho salmon ( Oncorhynchus kisutch ) - Chase R. Williams; Andrew H. Dittman; Paul McElhany; D. Shallin Busch; Michael T. Maher; Theo K. Bammler; James W. MacDonald; Evan P. Gallagher (Global Change Biology, 2019)
Elevated concentrations of CO 2 in seawater can disrupt numerous sensory systems in marine fish. This is of particular concern for Pacific salmon because they rely on olfaction during all aspects of their life including during their homing migrations from the ocean back to their natal streams. We investigated the effects of elevated seawater CO 2 on coho salmon ( Oncorhynchus kisutch ) olfactory‐mediated behavior, neural signaling, and gene expression within the peripheral and central olfactory system. Ocean‐phase coho salmon were exposed to three levels of CO 2 , ranging from those currently found in ambient marine water to projected future levels. Juvenile coho salmon exposed to elevated CO 2 levels for 2 weeks no longer avoided a skin extract odor that elicited avoidance responses in coho salmon maintained in ambient CO 2 seawater. Exposure to these elevated CO 2 levels did not alter odor signaling in the olfactory epithelium, but did induce significant changes in signaling within the olfactory bulb. RNA‐Seq analysis of olfactory tissues revealed extensive disruption in expression of genes involved in neuronal signaling within the olfactory bulb of salmon exposed to elevated CO 2 , with lesser impacts on gene expression in the olfactory rosettes. The disruption in olfactory bulb gene pathways included genes associated with GABA signaling and maintenance of ion balance within bulbar neurons. Our results indicate that ocean‐phase coho salmon exposed to elevated CO 2 can experience significant behavioral impairments likely driven by alteration in higher‐order neural signal processing within the olfactory bulb. Our study demonstrates that anadromous fish such as salmon may share a sensitivity to rising CO 2 levels with obligate marine species suggesting a more wide‐scale ecological impact of ocean acidification.

Evaluating markers of epithelial-mesenchymal transition to identify cancer patients at risk for metastatic disease - Evan L. Busch; Temitope O. Keku; David B. Richardson; Stephanie M. Cohen; David A. Eberhard; Christy L. Avery; Robert S. Sandler (Clinical & Experimental Metastasis, 2016)